Mapping Global Research Trends in Vocational Attitude Maturity: A Bibliometric and Scientometric Analysis - Bairagi, Sankar; Shahi, Raj Sharan (Journal of Data Science, Informetrics, and Citation Studies, 2026)
In an era characterised by technological transformation, changing labour-market dynamics, and increasing emphasis on employability and lifelong learning, vocational attitude maturity has emerged as a crucial determinant of career preparedness and successful educational-to-work transitions. This paper presents a bibliometric and scientometric analysis of global research trends in vocational attitude maturity. A total of 1,000 publications related to vocational attitude maturity published between 1920 and 2026 were retrieved from the Scopus and Web of Science Core Collection (WoSCC) databases on 15 July 2026 and analysed using VOSviewer software (Version 1.6.20) and Microsoft Excel. The study reveals a substantial increase in scientific production during recent decades, indicating growing scholarly interest in vocational attitude maturity, career development, and employability research. The United States (218 publications) and India (214 publications) emerged as the most productive countries in this field. Co-authorship analysis indicates a fragmented collaborative structure characterized by limited international research partnerships. Citation analysis identified John L. Holland (1,245 citations) and Mark L. Savickas (1,132 citations) as the most influential authors, while the Journal of Vocational Behavior emerged as both the most productive and the most cited source of publications. The most frequently occurring keywords in vocational attitude maturity research were vocational attitude maturity, career maturity, vocational maturity, career counselling, and vocational guidance, whereas employability, career adaptability, and psychological well-being emerged as contemporary research themes. The findings provide a comprehensive understanding of the intellectual structure, thematic evolution, and global research dynamics of vocational attitude maturity and offer valuable directions for future research, educational policy, and career guidance practices.
Keywords: Bibliometric Analysis; Career Development; Employability; Scientometric Analysis; Vocational Attitude Maturity; VOSviewer